HOUT-31. CARE PATTERNS AND TREATMENT EFFICACY: A CLINICAL SERIES OF PRIMARY GLIOBLASTOMA WITH AN EMPHASIS ON OLDER ADULTS. (5th November 2018) - Hultman, Meghan; Babcock, Anna; Anna, Lintelmann; Trusheim, John; Bruns, Patricia; Banerji, Nilanjana
Abstract: INTRODUCTION: Research suggests that glioblastoma (GBM) patients enrolled in clinical trials have better-than-average prognosis. However, since implementation of the Stupp protocol and approval of bevacizumab as second-line treatment, there have been limited reports of outcomes-related data for GBM patients in a real-world, multidisciplinary clinical setting. We report here care patterns and outcomes in patients with GBM in a real-world setting. METHODS: From October 2015 to March 2018, 47 patients with primary GBM treated at Abbott Northwestern Hospital were enrolled in this study. Demographic, pathologic, and clinical information was abstracted from electronic medical records. Quality of life was measured at specified time-points during treatment with the MDASI-BT questionnaire. Additional data analysis was performed for a subgroup of ≥65 year old patients. RESULTS: Median patient age was 58 years (range, 23–80) and 25.5% were aged ≥65 years. Gross total tumor resection was achieved in 91.5% patients and a majority of the patients received 6 weeks of chemoradiation post-surgery. Patients received adjuvant temozolomide for a median of 7 cycles (range, 2–18). MGMT-methylation was observed in 32% cases. Second-line therapy consisted of bevacizumab with/without carboplatin in 63.2% patients and 15 patients received TTFields treatment. Median progression-free survival (PFS) in this series was 8.9 months in all patients and 9.6 months in patient aged ≥65 years. Median overall survival (OS) was 22.4 months for both the full-cohort and elderly subgroup. Patients with MGMT-methylated tumors had a longer median PFS and OS, but the differences were not statistically significant. Three or more moderate to severe treatment related symptoms were observed in 51.8% patients. CONCLUSION: PFS and OS in this real-world setting were comparable to outcomes noted in controlled clinical trials. These results indicate that favorable survival rates in GBM patients, including elderly individuals, may be achieved with a multidisciplinary treatment approach.